Understanding diversity patterns in bacterioplankton communities from a sub-Antarctic peatland - Quiroga, María Victoria (2015)
Bacterioplankton communities inhabiting peatlands have the potential to influence local ecosystem functions. However, most microbial ecology research in such wetlands has been done in ecosystems (mostly peat soils) of the Northern Hemisphere, and very little is known of the factors that drive bacterial community assembly in other regions of the world. In this study, we used high-throughput sequencing to analyse the structure of the bacterial communities in five pools located in a sub-Antarctic peat bog (Tierra del Fuego, Argentina), and tested for relationships between bacterial communities and environmental conditions. Bacterioplankton communities in peat bog pools were diverse and dominated by members of the Proteobacteria, Actinobacteria, Bacteroidetes and Verrucomicrobia. Community structure was largely explained by differences in hydrological connectivity, pH and nutrient status (ombrotrophic versus minerotrophic pools). Bacterioplankton communities in ombrotrophic pools showed phylogenetic clustering, suggesting a dominant role of deterministic processes in shaping these assemblages. These correlations between habitat characteristics and bacterial diversity patterns provide new insights into the factors regulating microbial populations in peatland ecosystems.